2019
DOI: 10.1029/2019ja027320
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the Equatorial Electrojet on Auroral Activity and In Situ Solar Insulation

Abstract: By using 10 years of Challenging Minisatellite Payload satellite observations, we investigate the average conditions of the interplanetary magnetic field (IMF) prevailing during the westward counter equatorial electrojet (CEJ). Equally, we compared the average IMF conditions accompanying high-latitude field-aligned currents of the Region 1 (R1) and Region 2 (R2). It shows that both CEJ and high-latitude field-aligned currents events when R2 is greater than R1 tend to happen preferably during the northward turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 53 publications
2
46
0
Order By: Relevance
“…5a, but for the electron energy flux distribution in the southern hemisphere Fig. 5 (continued) dusk sides, which is consistent with the previous findings (e.g., Christiansen et al 2002;Le et al 2010;Wang et al 2019). All these comparisons further support the reliability of the DMSP FACs.…”
Section: Observationssupporting
confidence: 89%
“…5a, but for the electron energy flux distribution in the southern hemisphere Fig. 5 (continued) dusk sides, which is consistent with the previous findings (e.g., Christiansen et al 2002;Le et al 2010;Wang et al 2019). All these comparisons further support the reliability of the DMSP FACs.…”
Section: Observationssupporting
confidence: 89%
“…Various mechanisms have been proposed to explain the storm‐time EEJ, including zonal and meridional winds (e.g., Anandarao & Raghavarao, 1987; Wang et al., 2019). During a geomagnetic storm, the high‐latitude Joule heating and ion‐drag force can trigger disturbances in the coupled I–T system and the disturbance wind can travel to low latitudes and alter equatorial dynamo electric fields and currents (Blanc & Richmond, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…The potential roles of SAPS in the high-to low-latitude coupling of the upper atmosphere and its impact on the CEJ have been investigated in several previous studies. For example, Wang et al (2019) used 10year CHAMP observations and reported that the CEJ occurrence rate during SAPS is double compared with that under normal conditions, indicating the potential effects of SAPS. However, the internal physical mechanisms of the CEJ changes during the SAPS period have not been elucidated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wang H et al (2019) used 10 years of CHAMP observations to investigate how the counter equatorial electrojet (CEJ) depends on interplanetary magnetic field (IMF) conditions. The longitudinal distribution of the equatorial electrojet (EEJ) is closely modulated by the solar zenith angle.…”
Section: Ionospheric Dynamics and Couplingsmentioning
confidence: 99%